Coping with Secondary Traumatic Stress by General Duty Police Officers: Practical Implications - Conn, Stephanie M.; Butterfield, Lee D. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study used the Critical Incident Technique to examine the factors that helped, hindered, or might have helped 10 general duty police officers to cope with secondary traumatic stress. The data were best represented by 14 categories: self-care, family/significant other support, talking with co-workers, emotional engagement, work environment, mental health resources, personality, ability to help the victim, relatability to the victim, scene reminders, continuous exposure/dwelling, exposure to human nature, vulnerability of the victim, and presence of additional stressors. The findings are presented and recommendations are offered for counsellors working with this population and for police agency administrators.